Association between ultrasonographically measured visceral fat tissue thickness and proinflammatory adipokines in obesity - Crnobrnja Veljko; Ilinčić Branislava; Stokić Edita; Basta-Nikolić Marijana; Slankamenac Sonja; Stojšić-Milosavljević Anastazija; Žeravica Radmila; Čabarkapa Velibor (Vojnosanitetski Pregled)
Background/Aim. Obesity status can be assessed with numerous anthropometric, morphological and functional indices and this study was designed to assess relationship among them. The aim of this study was to investigate associations between anthropometric indices, ultrasonography measurement of visceral and subcutaneous fat tissue thickness and certain proinflammatory adipokines level. Methods. This cross-sectional study comprised a consecutive sample of 60 obese respondents without obesity-related comorbidities, and 20 age-matched healthy normal-weight controls. Anthropometric [body mass index (BMI), waist circumference (WC), neck circumference (NC), body fat, a body shape index (ABSI)], and ultrasonographic indices [thickness of intraabdominal fatt tissue (IAFT), visceral fat (VF), maximum subcutaneous fat (Max SFT), minimal subcutaneous fat (Min SFT)], and serum levels of chemerin and resistin were assessed in all subjects. Results. All anthropometric indices showed statistically significant differences between study groups. The mean IAFT, Max SFT, Min SFT and VF were significantly higher in the obese group compared to controls (p < 0.01, for all). Serum levels of chemerin and resistin correlated positively with BMI, percentage of fat adipose tissue (FAT, %), total FAT (kg), and VF (p < 0.05, for all). Also, we observed significant correlation between resistin and NC (r = 0.23, p = 0.03) and ABSI (r = 0.22, p = 0.04). In multivariable linear regression analysis, chemerin (β = 0.23; p = 0.008) and resistin (β = 0.43; p =0.002) were independently and significantly associated only with VF. Conclusion. Obesity indices, both classical and newer ones, are in positive, statistically significant correlation with the level of proinflammatory cytokines. Ultrasonographically measured VF thickness, independently associated with adipokine levels, may improve assessment of proinflammatory fat tissue characteristics. Further studies are needed to precisely define the use of ultrasonographic fat tissue measurements into clinical practice.